A History of an Historian through the Eyes of Another Historian: A Reader’s Gleanings - Šmahel, František (Dějiny – teorie – kritika, 2008)
In a somewhat autobiographical essay on the memoirs of the medievalist Aaron Yakovlevich Gurevich, the author meditates on the development of research into medieval history in eastern Europe in the second half of the twentieth century. In the light of Gurevich’s career and his own experience, the author poses the question of whether it is possible to research freely without the protection of a powerful patron. In addition, he comments briefly on the gradual penetration of west European, particularly French, methodological innovations into Soviet and Czech historiography. He demonstrates that even in these ideologically limited worlds an historian could nevertheless develop these foreign impulses in his or her own way. The author insightfully also considers the meaning of the relationship between Gurevich and Le Goff.